DIGITAL TECHNOLOGIES AND PEDAGOGICAL PRACTICES IN THE INFORMATION TECHNOLOGY FOR INTERNET TECHNICAL COURSE INTEGRATED TO HIGH SCHOOL: usages and discourses - Ivonilde Pereira Mota Alkmim; Denise Aparecida Brito Barreto; Cláudia Vivien Carvalho de Oliveira Soares (Universidade Federal de Sergipe, 2018)
We start from the assumption that interactivity can potentialize pedagogical practices. In this way, this article presents the results of a research that sought to discuss the practices mediated by digital technologies and the discourses that have permeated their usages in the Information Technology for Internet Technical Course integrated to High School at the Federal Institute of Northern Minas Gerais (IFNMG), Januaria Campus. This text addresses the issue of discourse from the Bakhtinian perspective and dialogues with authors who consider digital technologies as interfaces that support the process of teaching-learning.